2013
DOI: 10.1371/journal.pone.0069282
|View full text |Cite
|
Sign up to set email alerts
|

Primary Respiratory Chain Disease Causes Tissue-Specific Dysregulation of the Global Transcriptome and Nutrient-Sensing Signaling Network

Abstract: Primary mitochondrial respiratory chain (RC) diseases are heterogeneous in etiology and manifestations but collectively impair cellular energy metabolism. Mechanism(s) by which RC dysfunction causes global cellular sequelae are poorly understood. To identify a common cellular response to RC disease, integrated gene, pathway, and systems biology analyses were performed in human primary RC disease skeletal muscle and fibroblast transcriptomes. Significant changes were evident in muscle across diverse RC complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 80 publications
7
61
0
Order By: Relevance
“…This is supported by transcriptomic studies of cells and tissues from mitochondrial disease patients demonstrating tissue-specific patterns of transcriptional dysregulation. 94 …”
Section: Established Molecular Defects Indicate a Common Disorder Of mentioning
confidence: 99%
See 3 more Smart Citations
“…This is supported by transcriptomic studies of cells and tissues from mitochondrial disease patients demonstrating tissue-specific patterns of transcriptional dysregulation. 94 …”
Section: Established Molecular Defects Indicate a Common Disorder Of mentioning
confidence: 99%
“…Recent studies have demonstrated that PDHc and OXPHOS defects can induce transcriptional dysregulation of multiple cellular pathways including those that regulate RNA and protein metabolism. 94 These disturbances in cellular metabolism appear to be primarily mediated by effects on pathways responsible for sensing and responding to nutrient availability, including effects on the expression and activity of regulator of cellular growth mTORC1. 94 Treatment with rapamycin, an inhibitor of mTORC1, improved lifespan and attenuated neurodegeneration in the Ndufs4 knockout mouse model of LS, 97 supporting the notion that dysregulation of these pathways contributes to pathogenesis.…”
Section: Insights Into Broader Cellular Dysfunction: An Emerging Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Various bioinformatic analyses of transcriptome data sets of the mitochondrial dysfunction indicate that the central pathway related to ATP-generating network lies with AKT/mTORC (mammalian target of rapamycin complex) pathways. [ 18,19 ] Considering the involvement of AKT in both ATP generation and the inhibition of apoptosis in cells, we investigated the mechanism of PEGylated glucose action by probing the protein/expression of AKT1 and some apoptotic markers. Our results indicated that application of PEGylated glucose led to a 50% decrease of pAKT levels at the protein level, in correlation with an increase in cell death.…”
Section: Discussionmentioning
confidence: 99%